Sulfonated red and far-red rhodamines to visualize SNAP- and Halo-tagged cell surface proteins. Issue 30 (21st February 2022) - Birke, Ramona; Ast, Julia; Roosen, Dorien A.; Lee, Joon; Roßmann, Kilian; Huhn, Christiane; Mathes, Bettina; Lisurek, Michael; Bushiri, David; Sun, Han; Jones, Ben; Lehmann, Martin; et al.
Abstract : Sulfonated rhodamine dyes allow SNAP- and Halo-tag labelling of cell surface protein fusions. A far-red version can be used for STED nanoscopy. Abstract : The (in)ability to permeate membranes is a key feature of chemical biology probes that defines their suitability for specific applications. Here we report sulfonated rhodamines that endow xanthene dyes with cellular impermeability for analysis of surface proteins. We fuse charged sulfonates to red and far-red dyes to obtain Sulfo549 and Sulfo646, respectively, and further link these to benzylguanine and choloralkane substrates for SNAP-tag and Halo-tag labelling. Sulfonated rhodamine-conjugated fluorophores maintain desirable photophysical properties, such as brightness and photostability. While transfected cells with a nuclear localized SNAP-tag remain unlabelled, extracellular exposed tags can be cleanly visualized. By multiplexing with a permeable rhodamine, we are able to differentiate extra- and intracellular SNAP- and Halo-tags, including those installed on the glucagon-like peptide-1 receptor, a prototypical class B G protein-coupled receptor. Sulfo549 and Sulfo646 also labelled transfected neurons derived from induced pluripotent stem cells (iPSCs), allowing STED nanoscopy of the axonal membrane. Together, this work provides a new avenue for rendering dyes impermeable for exclusive extracellular visualization via self-labelling protein tags. We anticipate that Sulfo549, Sulfo646 and their congeners will be useful for a number of cell biology applications where labelling of intracellular sites interferes with accurate surface protein analysis.